2005
DOI: 10.1152/ajpregu.00441.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of tubular sodium reabsorption leading to “primary” hypertension: from gene polymorphism to clinical symptoms

Abstract: Bianchi, Giuseppe. Genetic variations of tubular sodium reabsorption leading to "primary" hypertension: from gene polymorphism to clinical symptoms. Am J Physiol Regul Integr Comp Physiol 289: R1536-R1549, 2005. doi:10.1152/ajpregu.00441.2005.-The definition of the most appropriate strategy to demonstrate causation of a given geneticmolecular mechanism in a complex multifactorial polygenic disease like hypertension is hampered by the underestimation of the complexity arising from the genetic and environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 161 publications
(226 reference statements)
4
47
0
Order By: Relevance
“…In this context, we have contributed to unraveling the role of a polymorphism of the cytoskeletal protein adducin and high levels of endogenous ouabain (EO) in hypertension and glomerular podocyte damage, both in animal models and in patients (Bianchi et al, 1994;Bianchi, 2005;Manunta et al, 2009;Ferrandi et al, 2010a,b). These studies have shown that mutant a-adducin and ouabain activate Src tyrosine kinase and the Src-dependent Na,K-ATPase phosphorylation and its signaling network, associated with an overall increase of renal tubular sodium reabsorption and blood pressure (BP) (Ferrandi et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have contributed to unraveling the role of a polymorphism of the cytoskeletal protein adducin and high levels of endogenous ouabain (EO) in hypertension and glomerular podocyte damage, both in animal models and in patients (Bianchi et al, 1994;Bianchi, 2005;Manunta et al, 2009;Ferrandi et al, 2010a,b). These studies have shown that mutant a-adducin and ouabain activate Src tyrosine kinase and the Src-dependent Na,K-ATPase phosphorylation and its signaling network, associated with an overall increase of renal tubular sodium reabsorption and blood pressure (BP) (Ferrandi et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Within this large distance, many haplotype blocks were included (39). Positive results were also obtained in 18 of 20 association studies that, in addition to BP, investigated variables that reflect body sodium or the renin-angiotensin system (16,26). Four of five studies (40 -44) showed an association between ␣-adducin polymorphism and organ damage in hypertensive individuals.…”
Section: Impact Of Adducin Family Genes On Human Hypertensionmentioning
confidence: 94%
“…According to a PubMed literature search, after our initial report (16,26), at least 67 articles addressed the association between human hypertension and the ADD1 Trp allele. Six human (20,30 -34) linkage studies showed positive results when a DNA marker that mapped to 30 kb from the ADD1 locus or SNP of one of the three adducin genes was considered either alone or in combination with each other or angiotensinconverting enzyme D allele or salt intake.…”
Section: Impact Of Adducin Family Genes On Human Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations